Group Communication’s Impact on 2022 Communication Science Students’ Motivation at the National University of Indonesia - Tiara Rosita Dewi; Arya Purwana; Syallwa Pratiwi; Wafie Rahma Dewie (Jurnal Komunikasi dan Bisnis, 2026)
This study investigated the relationship between group communication and learning motivation among Communication Science students (2022 cohort) at the National University of the Republic of Indonesia. Utilizing a quantitative descriptive frameworks, the study evaluates the degree to which interpersonal group dynamics stimulate student motivations and analyzes the statistical weight of this connetion. The results indicate that streamlined communication within groups is closely linked to higher levels of motivation. Ultimately, this work offers insight into the role of collaborative discourse in boosting student in boosting student involvement and academic performance.